Role of magnesium sulfate in neuroprotection in acute ischemic stroke - Harpreet Singh (Annals of Indian Academy of Neurology, 2012)
Aims: To study the effect of intravenous magnesium sulfate infusion on clinical outcome of patients of acute stroke. Materials and Methods: Sixty consecutive cases of acute ischemic stroke hospitalised within 24 h of an episode of stroke were taken as subjects. All subjects underwent a computed tomography head, and those found to have evidence of bleed/space-occupying lesions were excluded from the study. The subjects taken up for the study were divided into two groups of 30 subjects each. Both the groups received the standard protocol management for acute ischemic stroke. Subjects of Group 1 additionally received intravenous magnesium sulfate as initial 4 g bolus dose over 15 min followed by 16 g as slow infusion over the next 24 h. In all the subjects of the two study groups, serum magnesium levels were estimated at the time of admission (Day 0), Day 1 and Day 2 of hospitalization using an atomic absorption spectrometer. Statistical Analysis Used: Scandinavian stroke scores were calculated on Day 3, day of discharge and Day 28. Paired t-test was employed for comparison of stroke scores on Day 3, day of discharge and Day 28 within the same group and the unpaired t-test was used for the intergroup comparison, i.e. comparison of stroke scores of control group with corresponding stroke scores of magnesium group. Results: Comparison of stroke scores on Day 3 and day of discharge, on the day of discharge and Day 28 and on Day 3 and Day 28 in the magnesium group produced a t-value of 5.000 and P <0.001, which was highly significant. However, the comparison of the mean stroke scores between the magnesium and the control groups on Day 3, day of discharge and Day 28 yielded a P-value of >0.05, which was not significant. Conclusions: The study failed to document a statistical significant stroke recovery in spite of achieving a significant rise in serum magnesium level, more than that necessary for neuroprotection, with an intravenous magnesium sulfate regime.